Governação territorial e desenvolvimento sustentável nas regiões periféricas: Desafios económicos e institucionaisELOPMENT IN PERIPHERICAL REGIONS: ECONOMIC AND INSTITUTIONAL CHALLENGES - Oliveira, Pedro (Tourism and Hospitality International Journal, 2023)
This research aims to investigate how territorial governance can induce sustainable development, bearing in mind the challenge of smart growth and lasting employment creation, de-carbonization of economy and touristic valuation of intangible assets embedded in a certain territory. By analysing regional cases of sustainable management (the Tagus wine route and the River Sorraia’s Valley hydrographic harnessing), through literature review and direct observation, we argue that the Iberian institutions of education in partnership with scientific and technological poles play a strategic role to foster progress in scientific knowledge about effective solutions against climate change, including the overall sectors of economic activity. Furthermore, those institutions are also crucial to disseminate more environment friendly techniques of production by companies (particularly in micro- and small firms) and social economy organizations. The main point is that only a transparent process of negotiation open to all stakeholders - through creativity, entrepreneurship, spirit of citizenship and intergenerational solidarity - can lead to the maximization of the quality of life of people living in this part of Iberian territory